(untitled) (Texas Journal of Engineering and Technology, 2026)
The results of growing erbium-doped silicon epitaxial layers using two different growth modes are presented: conventional molecular beam epitaxy (MBE) and solid-phase epitaxy (SPE). It is shown that an erbium-doped silicon layer deposited by PFE on a cold substrate and subsequently annealed exhibits more intense photoluminescence at a wavelength of 1.54 µm than layers grown by MBE